Balanced Nutrition and Crop Production Practices for Closing Grain Sorghum Yield Gaps—East Central Kansas Experiment Field - B. McHenry; E. A. Adee; P. V. Vara Prasad; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2015)
A field experiment was conducted at the East Central Kansas Experiment Field near Ottawa, KS, and at the Kansas River Valley Experiment Field near Rossville, KS, in the summer of 2014 to evaluate diverse cropping systems approaches on closing sorghum yield gaps. Yield gaps can be understood as the difference between maximum yield and attainable on-farm yields. The factors that were tested include narrow row spacing; plant population; balanced nutrition practices, including various timings of nitrogen, phosphorus, and potassium (NPK) and micronutrient applications; crop protection with fungicide and insecticide applications; plant growth regulator effects; and the use of precision ag technology for maximizing yields, including a GreenSeeker meter (Trimble Navigation, Westminster, CO) for more precisely determining fertilizer nitrogen needs for sorghum. In addition, this project seeks to quantify the comparison between corn and grain sorghum grown side by side at two production input levels (low vs. high). Only sorghum grain yields are presented in this report. Grain sorghum yields were 115 to 135 bu/a in Rossville (under irrigation) and 60 to 80 bu/a in Ottawa (dryland). Rainfall was limited in Ottawa during the flowering and reproductive stages of growth, which drastically limited yield potential.
Keywords: sorghum; production practices; nutrients; yield